Paparan Gas Hidrogen Sulfida (H2S) dan Aktivitas Pemulung Terhadap Risiko Kesehatan Lingkungan di TPA Tahun 2022 - Fahmi, Rani Nabilla; Onasis, Aidil; merri, Suks; Muslim, Burhan; Zicof, Erick (Jurnal Kesehatan Lingkungan Mandiri, 2023)
Scavengers have the potential to be exposed to gases from the waste decomposition process at the final disposal area due to the activities of scavengers in the final disposal environment. Exposure to these gases can cause health problems for scavengers, one of which is due to Hydrogen Sulfide (H2S) gas. The purpose of the study was to determine the exposure of Hydrogen Sulfide (H2S) gas to scavengers at the Air Dingin final disposal area of Padang in 2022. The research method used Environmental Health Risk Analysis. The results of the three points measured were above the odor level limit value (0.02 ppm or 0.0278 mg/m3). The average realtime intake value is 1.55 x 10-3 mg/kg/day and the lifetime intake is 3.11 x 10-3 mg/kg/day. Realtime and lifetime RQ values, obtained RQ>1. This means that exposure to Hydrogen Sulfide (H2S) is not safe for scavengers. For this reason, it is necessary to carry out risk control efforts. For scavengers to use PPE, especially masks, and increase body resistance. For the Department of Environment of Padang, recommended to be able to monitor air quality related to polluting gases in the air around the final disposal area on a regular basis.